Molecular Detection of the K1 and K2 Capsular Serotypes and its Correlation with Biofilm Formation in Clinical Isolates of Klebsiella Pneumoniae - Mohammed, Mustafa Jasim; Mahmood, Suhad Saad (Iraqi Journal of Science, 2026)
Klebsiella pneumoniae is a Gram-negative bacterium and a member of the Enterobacteriaceae that can cause many infections. This research aimed to examine the effect of the presence of the K1 and K2 capsule serotypes on biofilm formation and its relation with resistance to antibiotics. In this study, 130 clinical specimens were collected from different clinical sources from patients in hospitals, and only 61 isolates were identified as K. pneumoniae by selective media, biochemical test, and Vitek II. Disc diffusion technique was used to assess the resistance of 61 isolates to ten distinct antibiotics. The greatest resistance was observed against Amoxicillin-clavulanate (98.36%), while the least resistance was noted for Meropenem (13.11%). Additionally, 95.08% of the isolated bacteria exhibited multidrug resistance (MDR). Microtiter plate method (MTP) was used to assess biofilm formation; 100% of the isolates were able to form biofilm, (13.11% 8/61) were strong biofilm producers, in comparison (65.57% 40/61) were moderate biofilm producers, and (21.31% 13/61) were weak biofilm producers. Using standard PCR, the wzck1 and cpsk2 genes were identified; the findings revealed that only three of the 61 isolates have been positive for K1 (wzck1), fifty-two for K2 (cpsk2), and Six for non-K1/K2. This study concludes that K. pneumoniae has a high ability to form a biofilm with varying levels, which in turn increases antibiotic resistance, as 95.08% of the isolates were MDR. Also, the capsule affects the biofilm formation, especially the K1 and K2 serotypes, as it shows higher levels of biofilm.